Exploring the Aldol Reaction in the Synthesis of Bioactive Compounds - A.B. Ferreira, Marco; C. Dias, Luiz; A. Leonarczyk, Ives; C. Polo, Ellen; C. de Lucca, Emilio (Current Organic Synthesis, 2015)
Carbonyl chemistry, specifically aldol reactions, is one of the most efficient and elegant strategies to build carbon-carbon bonds. In the last 15 years in Brazil, our research group and others have worked on the development and application of stereoselective aldol reactions, with direct application in the asymmetric synthesis of several natural products of biological interest. In this review, we highlight the major Brazilian contributions to this field.
Keywords: total synthesis